Availability and use of mycotoxin binders in selected urban and peri-urban areas of Kenya - Mutua, Florence K.; Lindahl, Johanna F.; Grace, Delia (Springer, 2019)
Aflatoxins are carcinogenic, toxic and immunosuppressive substances produced by some species of the fungal genus, Aspergillus. Consumption of aflatoxins can have serious health effects. Widespread in the tropical and sub-tropical world, aflatoxin B1 (AFB1) is found in many staple foods and feeds; after ingestion it is metabolized to aflatoxin M1 (AFM1), which transfers to milk. One option for reducing aflatoxin concentration in cow milk is addition of mycotoxin binders to animal feeds, but little is known about this practice in the smallholder dairy systems in developing countries. We undertook a study to investigate the availability and use of mycotoxin binders in selected urban and peri-urban areas of Kenya. Data were collected using key informant interviews with government officials and one-to-one questionnaire-guided interviews with agrovet outlets (shops that sell animal health products (such as antibiotics) and crop inputs (such as fertilizers) and feed processors. Nine different mycotoxin binder types were reported. They were sold by 8% (4/49) of agrovets and 33% (3/9) of feed processors. The binders were purchased by farmers formulating their own feeds and by feed processors. Our review of regulations found that incorporating binders into animal feeds is not mandatory and there are no specific standards governing their use in Kenya. Feed processors are expected to respect the maximum allowable limit of 5 μg/kg for AFB1 in complete feeds. Gaps in the local feed supplies that may potentially lead to increased risks of aflatoxin exposure through milk are discussed. This study provides key data on the availability and local use of mycotoxin binders, which were previously lacking. However, there is a need for continued research on their effectiveness in the local smallholder context, in order to promote their appropriate use.